Cyberpunk as a Subgenre of Science Fiction (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article is devoted to the cyberpunk as a type of science fiction and its development in the history of American literature. In this case there were studied several American writers’ works in this subgenre.